AlxTayOz Mixture Coatings Prepared Using Atomic Layer Deposition for Corrosion Protection of Steel1. Issue 4 (22nd May 2013) - Härkönen, Emma; Díaz, Belén; Światowska, Jolanta; Maurice, Vincent; Seyeux, Antoine; Fenker, Martin; Tóth, Lajos; Radnóczi, György; Marcus, Philippe; Ritala, Mikko; Knez, Mato; Yong, Qin
Abstract Atomic layer deposited (ALD) 50 nm AlxTayOz mixture coatings are grown on steel for corrosion protection. In morphological and compositional analyses the coatings are found to be uniform, conformal, well‐adhered, and low in defect density. Corrosion protection properties are evaluated with polarization measurements and neutral salt spray (NSS) testing. The sealing properties of the mixtures improve with increasing aluminum oxide content, whereas the protection durability improves with increasing tantalum oxide content. In comparison to single‐layer and nano‐laminate ALD Al2O3 and Ta2O5 coatings, all mixtures are found to have better protective properties.